Resolving structural ambiguity using animacy and grammatical cues in Chinese - Ong, Deborah Yoke Ting. (2012)
This study investigates how bilinguals resolve structural ambiguity in ambiguous Chinese relative clauses. Previous study has found cross-linguistic differences in the processing of ambiguous sentences such as “Somebody shot the servant of the actress who was on the balcony” (Cuetos & Mitchell, 1988). Some languages show preference for high attachment (the servant) while other languages such as Chinese has shown a preference for low attachment (the actress) (Shen, 2006). The role of animacy has also been found to be relevant in Chinese, with studies on the Competition Model supporting it as an important cue in agent identification (Bates et al., 1992). With two off-line questionnaire studies, this study looks at how the semantic animacy role and grammatical role (low attachment preference) affect ambiguity resolution in Chinese for both comprehension and production. It was found that animacy was a stronger cue for ambiguous Subject-extracted relative clauses while the grammatical cue was stronger for ambiguous Object-extracted relative clauses. The ambiguity resolution strategies of early English-Chinese bilinguals and that of L1 native Chinese speakers who are late bilinguals are also found to be largely similar.